Quality Control Analysis in Minimizing Production Complaints at PT. Betts Indonesia with Statistical Process Control Method - Ubaidillah, Habib; Rosyidi, Khafizh (Journal Knowledge Industrial Engineering (JKIE), 2024)
This study analyzes the implementation of quality control in PT. Betts Indonesia to minimize production complaints with the Statistical Process Control (SPC) method. Using a descriptive qualitative approach, the types of data were collected through several approaches, namely field observations, interviews with production staff, and analysis of complaint documents during the period from January 2021 to December 2021. The analysis was carried out using Statistical Process Control (SPC) tools including check sheets, Pareto diagrams, control maps, and fishbone diagrams. The results of the study identified critical defects such as Sideseam Failed by 29.8% and Wrong Label by 23.4% which accounted for at least 53.2% of the total complaints. Furthermore, the root cause analysis revealed four factors that were considered dominant, including: human error (improper machine operation), inconsistent materials (substandard raw materials), outdated methods (lack of standard procedures), and machine malfunction (old equipment). Recommendations include routine operator training, rigorous material inspections, process standardization, and preventive maintenance schedules.